Pelatihan dalam Mengasuh Kanak-Kanak Awal dengan Memiliki Emosional Yang Tinggi - Fauzian Nasution; Najwa Aulia; Nidaul Ummah; Putri Dirgahayu Pasaribu (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
If we talk about emotions then everyone will say that he has felt them. Everyone reacts to its existence. Human life is very rich in emotional experiences. Feelings and emotions are part of the entire human psychic aspect. This study aims as a psychological function of feelings and emotions that have an influence on other psychics such as observers, responses, thoughts and wills. Through qualitative research methods with a library research approach, understanding emotions helps children to guide their behavior in social situations and to talk about feelings. Emotions are reactions to a person or event. Emotions can be shown when feeling happy about something, angry at someone or afraid of something.